Reshaping vitreoretinal surgery: Intraoperative optical coherence tomography as a tool for enhancing surgical decision-making in complex cases - Yin-Hsi Chang; Gavin S. W. Tan; Hung-Da Chou; Andrew S. H. Tsai (Taiwan Journal of Ophthalmology)
Intraoperative optical coherence tomography (iOCT) has been applied and studied in a variety of vitreoretinal surgeries for its feasibility, safety, and outcomes for years. Common scenarios include membrane peeling procedures, retinal detachments, choroidal–retinal biopsies, Argus implants, and subretinal injections. iOCT offers the surgeon a better understanding of the retinal microarchitectural changes and timely intraoperative feedback, directing a future view of precision surgery. However, this technology has not been widely adopted due to its limitations including cost, surgeons’ habits, lack of compatible equipment, software limitations, and so on. We aim to highlight the importance of iOCT in guiding clinical-relevant surgical decisions by illustrating two vitreoretinal cases that are complex and less frequently encountered.